The Activation Method of Lactoperoxidase System to Inhibit Microbial Activity in Fresh Milk - Puspitarini, OR; Al-Baarri, AN; Legowo, AM; Bintoro, P; Hintono, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Lactoperoxidase system is antimicrobial system in milk. The LPO system has been succesfully applied in tropical regions to prolong the shelf life of milk. However, the LPOS activation is mostly conducted in the first hour of storage. In the case of milk processing manufacture, it takes up to 6 until 7 hours to preserve milk, therefore in this article, LPOS activation is discussed based on different activation time. The initial LPOS activation was conducted at the first and the third storage hour with formula of 0.25 ml of 0.0125 mM SCN-; 0.25 ml of 0.0125 mM H2O2 and 0.5 ml of 35 U/ml LPO in 9 ml of milk and the second activation was conducted with formula of 0.25 ml of 0.0125 mM SCN-; 0.25 ml of 0.0125 mM H2O2 and 0.5 ml of 35 U/ml LPO into 9 ml milk and formula 0.5 ml of 0.05 mM SCN-; 0.5 ml of 0.05 mM H2O2 and 1 ml of 35 U/ml LPO into 8 ml of milk at 30 °C. The result of research shows that the activation at the third hour with formula of 0.5 ml of 0.05 mM SCN-; 0.5 ml of 0.05 mM H2O2 and 1 ml of 35 U/ml LPO into 8 ml of milk can decrease total milk microbe up to below the standard of total fresh milk microbe that is 5.35x103 CFU/ml and pH level is 6.475. This research indicates that the LPOS activation at the third storage hour with formula of 0.5 ml of 0.05 mM SCN-; 0.5 ml of 0.05 mM H2O2 and 1 ml of 35 U/ml LPO can be used to inhibit the growth of milk microbes at 30 ° C, therefore, milk is safe to be consumed. Animal Production 15(2):119-126, May 2013